Chemogenetic manipulation of astrocyte activity at the synapse— a gateway to manage brain disease - Pereira, Maria João; Ayana, Rajagopal; Holt, Matthew G.; Arckens, Lutgarde (Frontiers in Cell and Developmental Biology, 2023)
Astrocytes are the major glial cell type in the central nervous system (CNS). Initially regarded as supportive cells, it is now recognized that this highly heterogeneous cell population is an indispensable modulator of brain development and function. Astrocytes secrete neuroactive molecules that regulate synapse formation and maturation. They also express hundreds of G protein-coupled receptors (GPCRs) that, once activated by neurotransmitters, trigger intracellular signalling pathways that can trigger the release of gliotransmitters which, in turn, modulate synaptic transmission and neuroplasticity. Considering this, it is not surprising that astrocytic dysfunction, leading to synaptic impairment, is consistently described as a factor in brain diseases, whether they emerge early or late in life due to genetic or environmental factors. Here, we provide an overview of the literature showing that activation of genetically engineered GPCRs, known as Designer Receptors Exclusively Activated by Designer Drugs (DREADDs), to specifically modulate astrocyte activity partially mimics endogenous signalling pathways in astrocytes and improves neuronal function and behavior in normal animals and disease models. Therefore, we propose that expressing these genetically engineered GPCRs in astrocytes could be a promising strategy to explore (new) signalling pathways which can be used to manage brain disorders. The precise molecular, functional and behavioral effects of this type of manipulation, however, differ depending on the DREADD receptor used, targeted brain region and timing of the intervention, between healthy and disease conditions. This is likely a reflection of regional and disease/disease progression-associated astrocyte heterogeneity. Therefore, a thorough investigation of the effects of such astrocyte manipulation(s) must be conducted considering the specific cellular and molecular environment characteristic of each disease and disease stage before this has therapeutic applicability.